Enhanced cisplatin resistance in oral-cancer stem-like cells is correlated with upregulation of excision-repair cross-complementation group 1 - Lo-Lin Tsai; Cheng-Chia Yu; Jeng-Fan Lo; Wen-Wei Sung; Huei Lee; Shiow-Ling Chen; Ming-Yung Chou (Elsevier, 2012)
Background/purpose: Oral squamous cell carcinoma (OSCC) is a prevalent cancer worldwide. Recent data suggest that a subpopulation of cancer cells, termed cancer stem cells (CSCs), is capable of initiating, maintaining, and expanding the growth of tumors. Importantly, CSCs confer chemo- and radioresistance. Cisplatin is the most widely used chemotherapeutic agent, and chemoresistance to cisplatin is one of the major causes of tumor recurrence and metastasis with OSCC. However, the role of oral-cancer stem-like cells (OC-SLCs) in the chemoresistance of OSCC has not determined. The aim of this study was to investigate a key player of chemoresistance in OC-SLCs. Materials and methods: OC-SLCs were isolated through sphere formation by cultivating the OC2 cell line in defined serum-free medium. Differential expression profiles of cell-surface stemness markers between enriched OC-SLCs and parental OSCC cells were elucidated by flow cytometry. Expression of excision repair cross-complementation group 1 (ERCC1) by OC-SLCs was examined by an RT-PCR and Western blotting. Results: Initially, significant sphere formation (OC-SLCs) was observed in OC2 cells. Enriched OC-SLCs highly expressed stem-cell surface markers (CD117 and CD133) and the ABC transporter gene (ABCG2). Enhanced chemoresistance to cisplatin was also noted in OC-SLCs. Further, the chemoresistance of OC-SLCs to cisplatin was possibly correlated with ERCC1 upregulation in OC-SLCs. Conclusions: In summary, these results suggest that OC-SLCs may play a vital role in tumor recurrence due to resistance to cisplatin. Additionally, ERCC1 upregulation might be involved in platinum resistance in oral CSCs.